2023
DOI: 10.3390/ma16041339
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Stability and Mechanical Behavior of Ultrafine-Grained Titanium with Different Impurity Content

Abstract: Ultrafine-grained (UFG) commercially pure (Ti Grade 2) and high-purity (Ti 99.99%) titanium can be a good alternative to less biocompatible Ti alloys in many biomedical applications. Their severe plastic deformation may lead to a substantial increase of strength, but their highly refined microstructure show a lower thermal stability which may limit their range of applications. The purpose of this study was to investigate the effect of interstitial elements on the thermal stability of UFG Ti Grade 2 and high-pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 58 publications
(85 reference statements)
1
1
0
Order By: Relevance
“…Furthermore, the microstructure of the 2-pass sample revealed a more refined structure than the 0-pass sample. This observation is consistent with the research, which indicated that multi-pass rolling leads to a refined microstructure and improved mechanical properties of titanium [77].…”
Section: Pore Sizesupporting
confidence: 93%
“…Furthermore, the microstructure of the 2-pass sample revealed a more refined structure than the 0-pass sample. This observation is consistent with the research, which indicated that multi-pass rolling leads to a refined microstructure and improved mechanical properties of titanium [77].…”
Section: Pore Sizesupporting
confidence: 93%
“…Commercially pure Ti is considered as a potent alternative to the commonly-used Ti-6Al-4 V alloy for biomedical applications owing to its low density, excellent corrosion resistance, inertness, and proper biocompatibility [1,2]. However, because of the low hardness and tensile strength, low fatigue strength, and poor tribological properties of CP-Ti, it is necessary to improve its mechanical and tribological properties through appropriate methods [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, additive manufacturing and dissimilar metal welding have attracted much attention for its various advantages, such as high efficiency and easy repeatability. Nonetheless, due to the manufacturing characteristics [5][6][7], mechanical anisotropy and performance distribution may become inhomogeneous and further deep microstructural characterizations should be performed.…”
mentioning
confidence: 99%